Drawn too extreme : an examination of the satire and the representations of the other in the works of Kurt Westergaard and Zapiro - Simonsen, Mikkel (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.